2022
DOI: 10.1155/2022/8223737
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits the Ferroptosis Pathway in Rat Bone Marrow Mesenchymal Stem Cells by Activating the PI3K/AKT/mTOR Signaling Axis to Attenuate Steroid-Induced Osteoporosis

Abstract: Steroid-induced osteoporosis (SIOP) is a form of secondary osteoporosis, but its specific mechanism remains unclear. Glucocorticoid (GC-)-induced death of osteoblasts and bone marrow mesenchymal stem cells (BMSCs) is an important factor in SIOP. Ferroptosis is an iron-dependent type of programmed cell death and can be induced by many factors. Herein, we aimed to explore whether GCs cause ferroptosis of BMSCs, identify pathways as possible therapeutic targets, and determine the underlying mechanisms of action. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…It also has inhibitory and stimulatory effects on cancer cell autophagy [ 21 ]. Several studies have illuminated the inhibitory effect of melatonin on ferroptosis in osteoporosis [ 22 ] and acute kidney injury [ 23 ], while the effect of melatonin on cancer cell ferroptosis has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It also has inhibitory and stimulatory effects on cancer cell autophagy [ 21 ]. Several studies have illuminated the inhibitory effect of melatonin on ferroptosis in osteoporosis [ 22 ] and acute kidney injury [ 23 ], while the effect of melatonin on cancer cell ferroptosis has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel context, our study found the downregulation of osteoclast differentiation, likely influenced by unicCa. 32 Regarding the STRING results, at 1 day, we identified a protein network linked to the MAPK cascade. It is worth noting that the PI3K-AKT and MAPK pathways exhibit numerous overlaps and crosstalk interactions, supporting various mechanisms of cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the PI3K-AKT and MAPK pathways exhibit numerous overlaps and crosstalk interactions, supporting various mechanisms of cell survival. 32 This interplay explains the disparities between the results obtained from DAVID and STRING analyses.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) showed that these receptors are expressed in bovine ovarian follicles and that melatonin binds to these receptors to promote the growth of secondary follicles. By binding to MT1 or MT2 receptors, melatonin can trigger several cellular responses, including activation of the PI3K/AKT pathway, which is related to maintenance viability and ultrastructure (Li et al., 2022). However, future studies are still need to evaluate the specific putative effect of melatonin in the activation of PI3K/AKT pathway in bovine early antral follicles.…”
Section: Discussionmentioning
confidence: 99%